Editorial: higher levels of certain serum bile acids in non‐alcoholic fatty liver disease–new insights from Guatemala.Authors' reply. Issue 2 (24th June 2022) - Rivera‐Andrade, Alvaro; Petrick, Jessica L.; Alvarez, Christian S.; Graubard, Barry I.; Florio, Andrea A.; Kroker‐Lobos, Maria F.; Parisi, Dominick; Freedman, Neal D.; Lazo, Mariana; Guallar, Eliseo; Groopman, John D.; Ramirez‐Zea, Manuel; et al.
LINKED CONTENT: This article is linked to Rivera–Andrade et al papers. To view these articles, visit https://doi.org/10.1111/apt.16948 and https://doi.org/10.1111/apt.16962